2010
DOI: 10.1002/pola.23889
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of donor–bridge–acceptor alternating copolymers containing perylene diimide units and their application to photovoltaic cells

Abstract: We have used Suzuki coupling to prepare a series of alternating copolymers featuring coplanar cyclopentadithiophene and hole-transporting carbazole units. We observed quenching in the photoluminescence spectra of our polymers after incorporating pendent electron-deficient perylene diimide (PDI) moieties on the side chains, indicating more efficient photoinduced electron transfer. Electrochemical measurements revealed that the PDI-containing copolymers displayed reasonable and sufficient offsets of the energy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
(87 reference statements)
0
26
0
Order By: Relevance
“…Thus, it's greatly desirable to explore new n‐type alternatives with good mobility and thermal stability for PSCs 13. Perylenediimide (PDI) and its derivatives are well‐studied n‐type organic semiconductors with high electron mobility,14–16 but their poor solubility makes them difficult to process. Some studies have reported to improve the solubility of perylene diimide via chemically incorporating substitutes into the N atoms of the imide groups or the bay positions in the PDI core 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it's greatly desirable to explore new n‐type alternatives with good mobility and thermal stability for PSCs 13. Perylenediimide (PDI) and its derivatives are well‐studied n‐type organic semiconductors with high electron mobility,14–16 but their poor solubility makes them difficult to process. Some studies have reported to improve the solubility of perylene diimide via chemically incorporating substitutes into the N atoms of the imide groups or the bay positions in the PDI core 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers consist of typical donor-type backbone and PDI side chain. Examples of donor-acceptor polymer architecture including polymers with PDI in the side chain were reported [23][24][25][26][27][28][29]. The results of BHJ OPV based on these polymers show the efficiency typically much less than 1%.…”
Section: Introductionmentioning
confidence: 99%
“…For hole mobility measurements, hole‐only devices were fabricated having the structure ITO/PEDOT:PSS/polymer/Au. The hole mobility was determined by fitting the dark J – V curve into the space‐charge‐limited current method,20, 40 based on the equation where ε 0 is the permittivity of free space, ε r is the dielectric constant of the polymer which is assumed to be around 3 for the conjugated polymers, μ h is the hole mobility, V is the voltage drop across the device, and L is the thickness of active layer.…”
Section: Methodsmentioning
confidence: 99%
“…In attempts to harvest more photons and to tune the energy levels, several conjugated polymers have been developed featuring electron donor/acceptor (D/A) units in main chain‐conjugated configurations9–19 and side‐chain‐attached architectures 20–24. Recently, some low‐band gap polymers have been developed to provide PCEs of up to 7% 25–29.…”
Section: Introductionmentioning
confidence: 99%